Does uterine preservation affect survival outcomes of patients with stage I ovarian sex cord-stromal cell tumours? A multi-institutional study. (November 2020) - Yoshihara, Masato; Tamauchi, Satoshi; Iyoshi, Shohei; Kitami, Kazuhisa; Uno, Kaname; Yoshikawa, Nobuhisa; Ikeda, Yoshiki; Kawai, Michiyasu; Nagasaka, Tetsuro; Kajiyama, Hiroaki
Abstract: Objective: Sex cord-stromal tumours of the ovary are relatively uncommon neoplasms that account for 3 % of all ovarian cancers. Uterine preservation with careful staging is achievable; however, conservative surgery remains controversial. This study examined the prognostic effects of uterine preservation in patients with stage I sex cord-stromal tumours. Study design: This retrospective cohort study was undertaken between January 1986 and February 2019, and the clinicopathological data of 4897 women with malignant ovarian tumours were collected. Seventy-seven patients with stage I sex cord-stromal tumours were eligible for inclusion. The characteristics and survival outcomes of these patients were examined. To investigate the prognostic effects of uterine-preserving surgery, baseline imbalances between patients with and without uterine-preserving surgery were adjusted using an inverse probability of treatment weighting with propensity scores composed of independent clinical variables. Results: The mean ages of patients in the uterine-preserving surgery and non-uterine-preserving surgery groups were 39.8 and 57.8 years, respectively. After inverse probability of treatment weighting adjustments, no significant differences in overall survival ( p = 0.205) or recurrence-free survival (p=0.071) were observed between the uterine-preserving surgery and non-uterine-preserving surgery groups. Estimated 10-year overall survival rates were 98.7 % in the uterine-preserving surgery group and 95.9 % in the non-uterine-preserving surgery group, and 10-year recurrence-free survival rates were 87.2 % in the uterine-preserving surgery group and 78.2 % in the non-uterine-preserving surgery group. Uterine-preserving surgery did not significantly affect the site of tumour recurrence. Conclusion: Uterine-preserving surgery may be a feasible surgical option for patients with stage I sex cord-stromal tumours. Further research is needed to guarantee prognostic accuracy and develop effective therapeutic approaches for sex cord-stromal tumours.